Narrativas para se deixar levar : o kitsch, o sentimentalismo e as comédias românticas - Guedes, Camila (2025)
This study investigates the use of kitsch in romantic comedy films as a strategy to provoke emotional experiences in the viewer. Starting from a personal and affective reflection on the genre, the research recognizes romantic comedies as cultural manifestations that are often undervalued, yet deeply connected to sentimentalism and the search for emotional comfort. The concept of kitsch—understood as an aesthetic linked to gentle emotions, nostalgia, and pleasure—is explored in relation to the genre, revealing key points of intersection. The research is grounded in the works of authors such as Humberto Eco, Abraham Moles, Laurent Julier, Robert Solomon, Michel Marie, and Tamar Jeffers McDonald, and adopts a qualitative approach, basic in nature, with descriptive objectives and bibliographic procedures. The chosen methodology is Poetic Analysis, proposed by Wilson Gomes, which emphasizes the effects of meaning produced by the work on the viewer. The analysis focuses on two representative films of the genre, My Best Friend’s Wedding (1997) and Anyone But You (2023), selected for their aesthetic, narrative, and emotional relevance. By examining elements such as soundtrack, archetypal characters, and the presence of exaggeration, the study seeks to understand how kitsch is employed in constructing the sentimentalism typical of romantic comedies and what effects this has on the reception of these works. Situated within the research line Production and Reception of Literary Texts of the Post Graduate Program in Language and Literature at the University of Passo Fundo, this study offers a defense of the cultural and affective legitimacy of the genre.